1999
DOI: 10.1007/s001250051204
|View full text |Cite
|
Sign up to set email alerts
|

Three new mutations in the hepatocyte nuclear factor-1α gene in Japanese subjects with diabetes mellitus: clinical features and functional characterization

Abstract: Mutations in the HNF-1alpha gene may affect the normal islet function by different molecular mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 21 publications
3
37
1
2
Order By: Relevance
“…The frameshift mutation was predicted to cause premature termination at codon 548. We also identified a conserved G to C replacement in the A site of the promoter (designated as +102G-to-C, relative to the transcription start site) which was reported previously [9]. None of these three mutations were found in the 100 control nondiabetic subjects.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…The frameshift mutation was predicted to cause premature termination at codon 548. We also identified a conserved G to C replacement in the A site of the promoter (designated as +102G-to-C, relative to the transcription start site) which was reported previously [9]. None of these three mutations were found in the 100 control nondiabetic subjects.…”
Section: Resultssupporting
confidence: 65%
“…We identified a +102G-to-C mutation, which has been reported previously [9]. This mutation was found in a diabetic patient, who was diagnosed as having diabetes at 8 years of age and was anti-GAD-positive.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In contrast, HNF-1α was expressed by all four kinds of endocrine cells, so it could regulate non-beta cells as well as beta cells in the pancreas. We previously reported that glucagon secretion was also impaired along with that of insulin in a MODY3 patient [41]. Isl1 and Pax6 are known to be expressed by all kinds of endocrine cells [22,26] but exocrine cells do not express these transcription factors.…”
Section: Discussionmentioning
confidence: 98%